Системний підхід щодо формування структури стратегічного потенціалу підприємства - Кравченко, А. М. (Ways to Improve Construction Efficiency, 2012)
The essence of the strategic potential of the company. Existing approaches to the definition of "strategic potential of the company." Compared study of domestic and foreign authors about forming a balanced strategic potential of the company. The basic and the most important factors shaping effective strategic potential of the company in an unstable environment.